Hemi-Jensen Procedure as Heavy Eye Syndrome Treatment: A Case Series: Poster Presentation - Case Series - Resident - Julita; Farhani, Harlin (Majalah Oftalmologi Indonesia, 2023)
Introduction : Heavy eye syndrome is an acquired myopia-associated strabismus characterized by esotropia and hypotropia accompanied by abduction and elevation limitations. This case series reports two heavy eye syndrome patients that underwent hemi-Jensen procedure combined with medial rectus recession with good postoperative result. Case Illustration : A 60-year-old female had right eye (RE) fixed inward and bilateral high myopia (S-13.00 D). RE Hirschberg test: >45° esotropia and hypotropia and RE axial length (AL) 28.3 mm. Second patient, a 53-year-old female, had both eyes fixed inward and bilateral high myopia (S-12.00 D). Both eyes Hirschberg test: >45° esotropia and hypotropia, left eye AL 31.4 mm, and prephthisis RE. Intraoperative identification of both patients revealed displacement of superior and lateral rectus muscles. No surgery performed on prephthisis eye. Hemi-Jensen procedure combined with medial rectus recession resulted in orthophoria (first patient) and central position in primary gaze (second patient), with improved ocular motility on both patients. Discussion : Heavy eye syndrome occurs in eyes with high myopia. The elongated globe in high myopia results in superotemporal herniation of the globe and superior and lateral rectus muscles displacement, which increases depression and adduction force. Hemi-Jensen procedure is a loop myopexy procedure which corrects the deviated muscle paths in heavy eye syndrome. Concurrent medial rectus recession can be performed with hemi-Jensen procedure if there is likely contracture of medial rectus. Conclusion : Heavy eye syndrome is a strabismus fixus condition which occurs in eyes with high myopia. Hemi- Jensen procedure is an effective treatment for heavy eye syndrome which improves ocular alignment and motility.